The History of Public Relations in China - Xue, Ke. author. aut Link
XIII, 250 p. 41 illus., 9 illus. in color.
Keywords: This book is the first on the history of Chinese public relations, and has been selected as one of the “40 representative books for 40 years of public relations in China” by the Public Relations Society of China. In four chapters, it systematically reviews and analyzes the trajectory and evolution of public relations in China from the very start – when the “reform and opening” policy was adopted in 1978 – to the present. The book will help both established and new scholars and practitioners in the field to understand the changing nature of public relations in China. It offers a unique perspective by placing the discussion of the development of public relations in the general context of the changes and development of China as a whole, and in relation to the changing status of public relations around the world. Accordingly, readers will not only gain a more in-depth understanding of the history of the field, but also of the political, economic, societal, cultural and scientificdevelopment of China in modern times.